On inverse factorization adaptive least-squares algorithms - Rontogiannis, Athanasios A.; Theodoridis, Sergios (Signal processing, 1996)
This paper presents an adaptive exponentially weighted algorithm for least-squares (LS) system identification. The algorithm updates an inverse ‘square root’ factor of the input data correlation matrix, by applying numerically robust orthogonal Householder transformations. The scheme avoids, almost entirely, costly square roots and divisions (present in other numerically well-behaved adaptive LS schemes) and provides directly the estimates of the unknown system coefficients. Furthermore, it offers enhanced parallelism, which leads to efficient implementations. A square array architecture for implementing the new algorithm, which comprises simple operating blocks, is described. The numerically robust behavior of the algorithm is demonstrated through simulations. The algorithm is compared to the recently developed inverse factorization QR scheme (Alexander and Ghirnikar, 1993), in terms of computational complexity, parallel potential and numerical properties. Ein adaptiver, exponentiell gewichteter Algorithmus zur Systemidentifikation auf der Basis kleinster Quadrate (least squares, LS) wird vorgestellt. Er führt einen inversen “Quadratwurzel”-Faktor der Eingangsdaten-Korrelationsmatrix nach, indem er numerisch robuste orthogonale Householder-Transformationen anwendet. Das Verfahren vermeidet nahezu vollkommen aufwendige Wurzel- und Divisionsschritte (wie sie in anderen numerisch gutmütigen adaptiven LS-Methoden auftreten) und liefert unmittelbar die Schätzwerte der unbekannten Systemkoeffizienten. Darüber hinaus bietet es einen verbesserten Parallelismus, der zu effizienten Realisierungen führt. Es wird eine quadratische Array-Architektur zur Realisierung des neuen Algorithmus beschrieben, welche einfache Funktionsblöcke umfaβt. Das numerisch robuste Verhalten des Algorithmus wird anhand von Simulationen demonstriert. Der Algorithmus wird mit dem kürzlich entwickelten inversen Faktorisierungs-QR-Schema (Alexander und Ghirnikar, 1993) im Hinblick auf Rechenaufwand, Parallelität und numerische Eigenschaften verglichen. Cet article présente un algorithme adaptatif avec pondération exponentielle pour l'identification de systèmes au sens des moindres carrés (LS). L'algorithme met à jour un facteur en ‘racine carrée’ inverse de la matrice de corrélation des données d'entrée, en appliquant des transformations orthogonales de Householder numériquement robustes. La méthode évite presque entièrement l'emploi de coûteuses divisions et racines carrées (que l'on rencontre dans d'autres méthodes LS adaptatives et numériquement robustes) et fournit directement les estimées des coefficients du système à identifier. De plus, il offre un parallélisme avancé menant à des implementations efficaces. On décrit une architecture de type matrice carrée comprenant de simples blocs opérateurs pour implémenter le nouvel algorithme. La robustesse numérique de l'algorithme est mise en évidence par des simulations. L'algorithme est comparé, à la méthode QR de factorisation inverse développée récemment (Alexander et Ghirnikar, 1993), en terme de complexité de calcul, de potentiel de parallélisme et de propriétés numériques.